URMC Universal Depression Screening Initiative: Patient Reported Outcome Assessments to Promote a Person-Centered Biopsychosocial Population Health Management Strategy - Van Orden, Kimberly A.; Lutz, Julie; Conner, Kenneth R.; Silva, Caroline; Hasselberg, Michael J.; Fear, Kathleen; Leadley, Allison W.; Wittink, Marsha N.; Baumhauer, Judith F. (Frontiers in Psychiatry, 2022)
Background. Patient-reported outcomes (PROs) can promote person-centered biopsychosocial health care by measuring outcomes that matter to patients, including functioning and well-being. Data support feasibility and acceptability of PRO administration as part of routine clinical care, but less is known about its effects on population health, including detection of unmet healthcare needs. Our objectives were to examine differences in rates of clinically significant depression across sociodemographic groups and clinical settings from universal depression screens in a large health system, estimate the number of patients with untreated depression detected by screenings, and examine associations between biopsychosocial PROs—physical, psychological, and social health. Methods. We analyzed data from over 200,000 adult patients who completed depression screens—either PROMIS (Patient Reported Outcomes Measurement Information System) or PHQ-2/9—as part of routine outpatient care. Results. Depression screens were positive in 14.2% of the sample, with more positive screens among younger versus older adults, women versus men, non-White versus White, and Hispanics versus non-Hispanics. These same sociodemographic indicators, as well as completing screening in primary care (versus specialty care) were also associated with greater likelihood of detected depression in the medical record. Discussion. Universal screening for depression symptoms throughout a large health system appears acceptable and has the potential to detect depression in diverse patient populations outside of behavioral health. Expanded delivery of PROs to include physical and social health as well as depression should be explored to develop a clinically-relevant model for addressing patients’ biopsychosocial needs in an integrated fashion across the health system.